2019
DOI: 10.1111/1750-3841.14696
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Basket Geometry on the Sensory Quality and Consumer Acceptance of Drip Brewed Coffee

Abstract: In this work, discrimination tests, descriptive analysis, consumer tests, and total dissolved solids (TDS) were used to evaluate the effects of brew basket geometry on the sensory quality and consumer acceptance of drip brewed coffee. Two basic geometries, semi‐conical and flat‐bottom, were evaluated in conjunction with coffee roast and particle size. Initial discrimination tests showed that small differences in median particle size were not discernable, but that coffees brewed using either semi‐conical or fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 23 publications
0
57
0
1
Order By: Relevance
“…Additionally, the highest intensity of rubber flavor was found in the dark roast coffees, but a significant response surface was only obtained for light and medium roast; thus, all dark roast coffees were perceived to have the same intensity of rubber flavor, but rubber flavor could be modified in the light and medium roast coffees by brewing. These four attributes (smoke/acrid aroma, tobacco flavor, woody flavor, and rubber flavor) are common descriptors of dark roast coffee, and their impact on consumer preference has previously been shown (Frost et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the highest intensity of rubber flavor was found in the dark roast coffees, but a significant response surface was only obtained for light and medium roast; thus, all dark roast coffees were perceived to have the same intensity of rubber flavor, but rubber flavor could be modified in the light and medium roast coffees by brewing. These four attributes (smoke/acrid aroma, tobacco flavor, woody flavor, and rubber flavor) are common descriptors of dark roast coffee, and their impact on consumer preference has previously been shown (Frost et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 1, the nine overlaid zones on the Brewing Control Chart each express a different brewing quality; for example, a brew with low PE and high TDS is designated as a "strong under developed" coffee, while a brew of high PE and low coffees from 14 different countries and comprises over 100 aroma and flavor attributes (Chambers et al, 2016). This flavor complexity stems from a wide variety of processing conditions throughout the production chain, including cultivar (Razafinarivo et al, 2013), various agronomic practices (Tolessa, D'heer, Duchateau, & Boeckx, 2017;Vaast, Bertrand, Perriot, Guyot, & Génard, 2006), postharvest processing (De Bruyn et al, 2017), roasting (Czerny & Grosch, 2000;Schenker et al, 2002), and brewing (Batali, Frost, Lebrilla, Ristenpart, & Guinard, 2020;Caprioli, Cortese, Sagratini, & Vittori, 2015;Fibrianto et al, 2019;Frost, Ristenpart, & Guinard, 2019), with each step impacting the final coffee flavor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors also reported that sensory differences in coffee were apparent preroasting, but became much more apparent following the roasting process. Furthermore, a recent study by Frost, Ristenpart, and Guinard () showed that product features have specific associated sensory effects. For example, brew basket design, independent from other features, significantly affected smoke aroma, sweetness, and tobacco flavors, while differing grind sizes and roasts had several uniquely connected sensory distinctions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have approached the differentiation of coffee consumer groups using various stimuli and methodologies. From a sensory perspective, consumer‐focused literature on coffee suggests that consumer groups are primarily differentiated by roast, with most consumers preferring an intermediate intensity with moderate bitterness and roasted flavors, while a smaller group prefers bolder, more intense coffees (Frost et al, ; Varela, Beltrán, & Fiszman, ). However, it should be noted that more specific secondary drivers for coffee consumer segments have been noted in the cited studies, among others.…”
Section: Introductionmentioning
confidence: 99%